Political discourse in Indonesia and Malaysia for national human security: a case study of Lahad Datu - Erman Anom,; Chang, Peng Kee; Julia Wirza Mohd Zawawi, (Universiti Kebangsaan Malaysian, 2014)
Issues related to the Malay world (Indonesia and Malaysia) and across the border in the context of political, economic and trade had been discussed and explored many times over. However, the national and regional human security issues within the Malay culture have been neglected. It received no or little coverage from the media. Thus, this research looked at the Indonesia-Malaysia political discourse in maintaining political stability within the Malay Archipelago. It will use document analysis to understand the role of the Indonesia-Malaysia political communication in maintaining the security of the Malay Archipelago by using the Lahad Datu issue as a case study. The study found that the political communication between Indonesia and Malaysia is vibrant. The style of political communication used was of mutual understanding of their respective roles, with less focus on sensationalism and more emphasis on conflict prevention.